(untitled) (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Self stigma occurs when people internalize the public attitudes and suffer numerous negative consequences as a result. The severe negative consequences of self-stigma are low self-esteem, increase in severity of symptoms, low treatment adherence and decrease quality of life . Thus, this study aims to find the prevalence of self-stigma and its effect on self-esteem of patients with alcohol use disorder (AUD). Method: A cross-sectional study (n=132) was conducted among patients with AUD attending psychiatric outpatient department (OPD) of Patan Hospital and Mental Hospital, Lagankhel. Non probability purposive sampling technique was used for the study. The data was collected by face-to-face interview technique using structured interview schedule . Descriptive statistics and inferential statistics (Pearson chi-square and Pearson correlation) were used for data analysis. Result: Among AUD patients, 97.8% had self-stigma. Among them 22% experienced mild, 45.5% moderate, and 30.3% severe self-stigma. Among the five components of self-stigma, alienation had highest mean score followed by discrimination experience and lowest in stigma resistance. Regarding self-esteem, 88.6% had low, 5.3% had moderate and only 6.1% had high self-esteem. There was a significant negative correlation (r=-.458)between self-stigma and self-esteem. Conclusion: Based on the study findings it is concluded that almost all of the patients with AUD had experienced self-stigma. More than three fourth of patients had low self-esteem and self-stigma is negatively correlated with self-esteem.